Perancangan Lanskap Ruang Terbuka Hijau Sarijadi Kecamatan Sukasari, Bandung, sebagai Taman Lingkungan - Rusiani, Nahla (Nusantara Journal of Science and Technology, 2024)
Population growth that is not balanced with improvements in the quality of infrastructure in urban areas causes irregularities in spatial and regional planning which have a negative impact on social and environmental conditions. The low level of public awareness of the environment has resulted in flooding problems, disease and impaired sensory perception due to waste. The aim of the design is to design the outdoor landscape as a green open space that can accommodate the activities of flat residents and Sarijadi Village, and educate residents with a garden about integrated waste processing for environmental sustainability. The design method used is synthetic analysis. The main potential is that the design land is located in a densely populated area and the problem is that there is an ecological imbalance in the area. Both are rooted in waste problems related to the daily life of every household in each settlement. Based on site analysis requirements, green open space design can be divided into three main parts; Sarijadi Village environmental park, flat garden as the entrance to Rusunawa Sarijadi RW 5, and outdoor space between the flat building blocks. The utility concept offered is processing household organic waste and culinary areas with a biogas digester into gas energy, electricity for flat and environmental garden activities, and compost for community gardens.